Dark calories : how vegetable oils destroy our health and how we can get it back - Shanahan, Catherine (Hachette Go, an imprint of Hachette Books, 2024)
"In recent years, on the heels of high profile revelations about nutrition gatekeepers and new technologies that are capable of measuring how foods are metabolized in the body, Dr. Cate has been shouting something new from the rooftops. If you are looking for the most powerful driver of the obesity and nearly all disease epidemics afflicting both young and old, you need look no further than the vegetable oils listed as main ingredients on the packages you buy. If you've had trouble losing weight, or experience heartburn, hypoglycemia symptoms, seasonal allergies, asthma, eczema, frequent headaches, or palpitations, just to name a few symptoms, your body may be giving you early warning signs that it's struggling to control the inflammation induced by seed oils. And that vegetable oil's meteoric rise in our food supply more perfectly parallels the explosion of obesity, diabetes, and other metabolic diseases than any other single variable in the modern diet equation. And it's time to expunge it, for good. Dark Calories is the first book to definitively show that vegetable oil is the defining ingredient in not just junk food but all processed food, from frozen meals, canned soup, pizza, and even your vitamin gummies, and makes the case that eliminating it is the single best thing you can do for your health. Through a narrative account of the speedy rise of the vegetable oil industry, a walk through the science of how it fundamentally alters our cells, and an action plan to help you take your health back into your own hands today, Dr. Cate shows how three factors-a combination of endless advertising sound bites, undisclosed conflicts of interest in research, and the failure of medicine to focus on prevention-have destroyed human health and turned nutrition science into a farce"--